Wood composite material and method of making and use thereof
Patent Information
- Application Number
- CN202611080561.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]然而,经上述增强改性剂处理后的木材,容易残留三聚氰胺和甲醛等毒性成分,反而劣化了木材自身的环保优势,并且,其受潮霉变问题未得到有效解决
本申请实施例提供的木质复合材料,其采用木材基体的纤维素三维骨架作为支撑结构,提供基础支撑和孔隙空间;纤维素三维骨架内填充有纤维增强材料,构成增强网络,承担力学增强功能;阻燃剂分散于骨架剩余孔隙中,提供阻燃保护;外层设置有疏水层,提供疏水、耐候、自清洁功能。上述各组分协同作用,使木质复合材料在保持木质基材环保属性的同时,还兼具优异的力学性能、阻燃性、疏水耐潮、自清洁性等优势,同时实现了力学、阻燃、耐候等多性能的同步跃升,满足目前工业产品,特别是汽车外饰件向着轻量化和环保化方向发展的需求。
Smart Images

Figure CN122975813A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of wood materials technology, and in particular to wood composite materials, their preparation methods and applications. Background Technology
[0002] As the automotive industry continues to develop towards lightweighting and environmental protection, wood, with its advantages of being lightweight, environmentally friendly, and biodegradable, is increasingly being used to manufacture automotive exterior parts.
[0003] Due to the inherent defects of wood, such as flammability, poor mechanical properties, and susceptibility to moisture and mold, related technologies use a mixture of melamine, formaldehyde, urea, soluble sodium silicate, and polyvinyl alcohol as a reinforcing modifier, and mix it with flame retardants to impregnate the wood, thereby enhancing its mechanical properties and imparting flame retardancy.
[0004] However, wood treated with the aforementioned reinforcing and modifying agents is prone to retaining toxic components such as melamine and formaldehyde, which degrades the wood's inherent environmental advantages. Furthermore, its problem of mold and mildew due to moisture has not been effectively resolved. Summary of the Invention
[0005] In view of this, this application provides a wood composite material, its preparation method and application, which can solve the technical problems existing in the related art.
[0006] Specifically, the following technical solutions are included: In a first aspect, a wood-based composite material is provided, the wood-based composite material comprising: The wood matrix has a three-dimensional cellulose skeleton; Fiber-reinforced material is filled within the three-dimensional cellulose skeleton; Flame retardant, filled within the three-dimensional cellulose skeleton; A hydrophobic layer, the hydrophobic layer covering the surface of the wood matrix; The density of the wood composite material is greater than or equal to 1.2 g / cm³. 3 .
[0007] In some possible implementations, the fiber-reinforcing material includes bamboo fiber and bamboo cellulose nanofibers bonded to the surface of the bamboo fiber.
[0008] In some possible implementations, the wood matrix has a density of less than or equal to 1 g / cm³. 3 It is obtained by partially removing lignin from natural wood.
[0009] In some possible implementations, the flame retardant includes at least one of phosphorus-based or nitrogen-based flame retardants.
[0010] In some possible implementations, the flame retardant includes polyethyleneimine and ammonium polyphosphate.
[0011] In some possible implementations, the hydrophobic layer comprises: a siloxane network and polydimethylsiloxane molecules wrapped around the siloxane network.
[0012] In some possible implementations, the fiber reinforcement material accounts for 3% to 15% of the mass percentage of the wood composite material; The flame retardant accounts for 10% to 20% of the mass percentage of the wood composite material.
[0013] In some possible implementations, the density of the wood composite material is 1.2 g / cm³. 3 ~1.4g / cm 3 .
[0014] Secondly, a method for preparing a wood-based composite material is provided, wherein the wood-based composite material is as described in the first aspect, and the method for preparing the wood-based composite material includes: Natural wood is subjected to lignin removal treatment to obtain a wood matrix with a three-dimensional cellulose skeleton; The first intermediate is obtained by filling the three-dimensional cellulose skeleton of the wood matrix with fiber-reinforced material. The flame retardant is filled into the skeleton of the first intermediate to obtain the second intermediate; The second intermediate is subjected to hot pressing to obtain the wood composite material.
[0015] In some possible implementations, the method for preparing the wood composite material further includes: After hot pressing, the obtained wood composite material is subjected to surface hydrophobic treatment to form a hydrophobic layer on the surface of the wood composite material.
[0016] Thirdly, a wooden structural component is provided, characterized in that the wooden structural component is prepared using the wood composite material described in the first aspect.
[0017] In some possible implementations, the structural component includes automotive exterior trim.
[0018] Fourthly, a vehicle is provided, the vehicle comprising the wooden structural components described in the third aspect.
[0019] The technical solution described in this application has at least the following beneficial effects: The wood-based composite material provided in this application uses a three-dimensional cellulose skeleton of a wood matrix as a supporting structure, providing basic support and porous space. Fiber-reinforcing materials are filled within the cellulose skeleton to form a reinforcing network, undertaking mechanical reinforcement. A flame retardant is dispersed in the remaining pores of the skeleton, providing flame retardant protection. An outer hydrophobic layer provides hydrophobicity, weather resistance, and self-cleaning properties. The synergistic effect of these components allows the wood-based composite material to maintain the environmentally friendly properties of the wood matrix while also possessing excellent mechanical properties, flame retardancy, hydrophobicity, moisture resistance, and self-cleaning properties. This achieves a simultaneous leap in mechanical, flame retardant, and weather-resistant properties, meeting the current demands of industrial products, especially automotive exterior parts, for lightweight and environmentally friendly designs. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 A flowchart illustrating the preparation process of an exemplary wood composite material and wood structural component provided in this application embodiment.
[0022] The accompanying drawings illustrate specific embodiments of this application, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the concept in any way, but rather to illustrate the concept of this application to those skilled in the art through reference to particular embodiments. Detailed Implementation
[0023] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0024] As the automotive industry moves towards lightweighting and environmental friendliness, traditional metal and plastic automotive exterior parts face challenges in resource consumption and recycling. Wood, as a natural and renewable material, boasts advantages such as being lightweight, environmentally friendly, and biodegradable, and is increasingly being used in the manufacture of automotive exterior parts. However, wood's inherent drawbacks, such as flammability, poor mechanical properties, and susceptibility to moisture and mold, limit its application in various scenarios, including automotive exteriors.
[0025] Because wood has inherent defects such as flammability, poor mechanical properties, and susceptibility to moisture and mold, it is usually modified by chemical means to solve these defects. For example, related technologies use a mixture of melamine, formaldehyde, urea, soluble sodium silicate, and polyvinyl alcohol as a reinforcing modifier, and mix it with flame retardants to impregnate the wood, thereby enhancing its mechanical properties and giving it flame retardancy.
[0026] However, wood treated with the aforementioned reinforcing and modifying agents is prone to retaining toxic components such as melamine and formaldehyde, which degrades the wood's inherent environmental advantages. Furthermore, its problem of mold and mildew due to moisture has not been effectively resolved.
[0027] This application addresses the inherent defects of natural wood, such as its flammability, poor mechanical properties, and susceptibility to moisture and mold, as well as the problem that traditional modification processes leave behind toxic melamine and formaldehyde, thus undermining its environmental advantages. It provides a novel pure wood composite material solution that achieves a dual improvement in comprehensive performance and environmental friendliness.
[0028] The wood-based composite material comprises: a wood matrix, fiber reinforcement, a flame retardant, and a hydrophobic layer. The wood matrix is obtained by removing at least a portion of the lignin from natural wood and has a three-dimensional cellulose skeleton. The fiber reinforcement fills within the cellulose skeleton. The flame retardant fills within the cellulose skeleton. The hydrophobic layer coats the surface of the wood matrix. Furthermore, the density of this wood-based composite material is greater than or equal to 1.2 g / cm³. 3 .
[0029] The wood-based composite material provided in this application has improved mechanical properties because, by performing a delignification treatment on the wood to retain the three-dimensional cellulose skeleton, and filling the skeleton with fiber-reinforcing materials, the fiber-reinforcing materials and the three-dimensional cellulose skeleton of the wood work synergistically to improve the mechanical properties of the wood-based composite material.
[0030] The wood-based composite material provided in this application has improved fire resistance, moisture resistance, and mildew resistance. This is because the flame retardant is filled into the three-dimensional cellulose skeleton in this application, giving the wood-based composite material good flame retardancy and effectively solving the problem of wood's flammability. At the same time, the surface of the wood-based composite material is coated with a hydrophobic layer. This hydrophobic layer not only effectively isolates moisture to prevent the wood from becoming damp and moldy, but also gives the material a self-cleaning function, which helps to reduce its maintenance costs and improve its long-term weather resistance.
[0031] The wood-based composite material provided in this application is environmentally friendly and safe. In view of the problem of toxic residues in traditional modifiers, this application abandons toxic chemical reinforcing agents and uses fiber-reinforcing materials that are safer and more environmentally friendly, thus giving the wood-based composite material both environmental friendliness and safety.
[0032] The wood-based composite material provided in this application uses a three-dimensional cellulose skeleton of a wood matrix as a supporting structure, providing basic support and porous space. Fiber-reinforcing materials are filled within the cellulose skeleton to form a reinforcing network, undertaking mechanical reinforcement. A flame retardant is dispersed in the remaining pores of the skeleton, providing flame retardant protection. An outer hydrophobic layer provides hydrophobicity, weather resistance, and self-cleaning properties. The synergistic effect of these components allows the wood-based composite material to maintain the environmentally friendly properties of the wood matrix while also possessing excellent mechanical properties, flame retardancy, hydrophobicity, moisture resistance, and self-cleaning properties. This achieves a simultaneous leap in mechanical, flame retardant, and weather-resistant properties, meeting the current demands of industrial products, especially automotive exterior parts, for lightweight and environmentally friendly designs.
[0033] The fiber reinforcement materials involved in the embodiments of this application can be natural fibers such as bamboo fiber, hemp fiber, and wood-derived cellulose nanofibers, or biodegradable polymer fibers (e.g., polylactic acid fiber). All of the above reinforcement materials can achieve excellent reinforcement effects while maintaining their safety and environmental protection advantages.
[0034] In some examples, the fiber-reinforcing materials include bamboo fibers and bamboo cellulose nanofibers bonded to the surface of the bamboo fibers.
[0035] Bamboo fibers typically carry a positive charge, while bamboo cellulose nanofibers typically carry a negative charge. The two can spontaneously combine through electrostatic attraction, allowing the bamboo cellulose nanofibers to be uniformly adsorbed and coated onto the surface of the bamboo fiber bundles, forming a composite reinforced bamboo fiber system. This electrostatic self-assembly process requires no additional adhesives, making it environmentally friendly and resulting in a strong bond. Simultaneously, the negatively charged bamboo cellulose nanofibers can also form hydrogen bonds and electrostatic interactions with the cellulose hydroxyl groups in the wood matrix, achieving a stable bond between the fiber reinforcement and the wood matrix, ensuring stable and long-term maintenance of its mechanical properties.
[0036] This scheme utilizes the principle of electrostatic self-assembly to construct a bamboo fiber reinforcement system. The bamboo fiber bundles (Q-Fiber) are positively charged on the surface through surface modification treatments such as quaternization; while the bamboo cellulose nanofibers (CCNF) are negatively charged by introducing carboxyl groups on the surface through carboxylation modification.
[0037] As mentioned above, the wood matrix is obtained by removing some of the lignin from natural wood. In some examples, the wood matrix has a density of less than or equal to 1 g / cm³. 3 It is obtained by partially removing lignin from natural wood. For example, the density of natural wood can be less than or equal to 0.8 g / cm³. 3 It can be further reduced to 0.6 g / cm³ 3 ~0.8g / cm 3 .
[0038] The embodiments of this application achieve a density of natural wood less than or equal to 1 g / cm³. 3 This type of natural wood has a high porosity. After the lignin removal treatment, lignin and at least some hemicellulose are removed, while its cellulose skeleton is preserved and the pores are further opened, forming a continuous three-dimensional network channel, which is conducive to the deep penetration and uniform filling of subsequent fiber reinforcement materials and flame retardants.
[0039] Some natural woods that meet the above density requirements include, but are not limited to: birch, poplar, paulownia, balsa wood, white linden, beech, black walnut, etc.
[0040] The lignin removal rate is 15wt%~50wt%, which can be 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, etc., and further, the lignin removal rate is 15wt%~30wt%. That is to say, lignin remains in the wood matrix. By partially removing lignin from natural wood, rather than removing it completely, the plasticity of the wood can be moderately improved to facilitate shaping, rather than creating extremely high porosity. At the same time, the natural texture and color of the wood can be better preserved.
[0041] The lignin removal process for natural wood can be carried out by placing the wood in a mixed solution of NaOH / Na2SO3 (the mass ratio of NaOH to Na2SO3 can be 3~8:1) and treating it under heating conditions for a specific time to remove lignin. The lignin removal rate can be controlled by adjusting the concentration of the treatment solution, the treatment temperature, and the treatment time.
[0042] For the aforementioned wood-based composite materials, the flame retardant can be a phosphorus-based flame retardant, a nitrogen-based flame retardant, a phytic acid-based flame retardant, an intumescent flame retardant, or an inorganic nanosheet flame retardant (such as layered double hydroxides).
[0043] In some examples, the flame retardant includes at least one of phosphorus-based or nitrogen-based flame retardants.
[0044] Phosphorus-based flame retardants decompose into phosphoric acid substances when heated, which can promote the dehydration and carbonization of wood cellulose and form a dense carbon layer to block heat and oxygen transfer; nitrogen-based flame retardants decompose when heated to release non-flammable gases such as ammonia and nitrogen, which dilute the concentration of flammable gases and carry away heat. Both types of flame retardants have good flame retardant effects.
[0045] Some suitable phosphorus-based flame retardants include, but are not limited to: ammonium polyphosphate (APP), guanidine phosphate, phosphate esters, phytic acid and its salts; some suitable nitrogen-based flame retardants include, but are not limited to: polyethyleneimine (PEI), urea, etc. These flame retardants are advantageous in maintaining the environmental friendliness of wood-based composite materials.
[0046] Depending on the actual flame retardant rating requirements, phosphorus-based or nitrogen-based flame retardants can be used alone, or they can be used in combination to achieve a synergistic flame retardant effect.
[0047] In some examples, the flame retardant includes polyethyleneimine and ammonium polyphosphate. For further examples, the mass ratio of polyethyleneimine to ammonium polyphosphate can be 1:1 to 1:5.
[0048] A nitrogen-phosphorus synergistic flame retardant system is developed using polyethyleneimine and ammonium polyphosphate. Polyethyleneimine, acting as the nitrogen source, contains numerous amino and imine groups in its molecular chain, releasing non-flammable gases such as ammonia upon thermal decomposition. Ammonium polyphosphate, a highly polymerized form, decomposes upon heating to release phosphoric acid and promote char formation. The combination forms a classic intumescent flame retardant system: upon heating, the phosphoric acid produced from the decomposition of ammonium polyphosphate acts as an acid source, while polyethyleneimine serves as both a gas source and a char source auxiliary, jointly promoting the dehydration, carbonization, expansion, and foaming of the wood substrate, forming a thick and dense porous char layer. This char layer effectively blocks heat and oxygen from entering the substrate and prevents combustible gases from escaping, resulting in high flame retardant efficiency.
[0049] For the hydrophobic layer, any known hydrophobic system can be used, such as siloxane hydrophobic systems, organosilicon hydrophobic systems, fluorocarbon hydrophobic systems, wax-based hydrophobic systems, etc.
[0050] In some examples, the hydrophobic layer comprises a siloxane network and polydimethylsiloxane molecules wrapped around the siloxane network.
[0051] Siloxane networks can be formed by the hydrolysis and condensation of tetraethoxysilane (TEOS). TEOS, as a precursor, undergoes a hydrolysis and condensation reaction catalyzed by ammonia to generate a silica network with a micro-nano-scale rough structure, providing the necessary roughness for superhydrophobic surfaces. Polydimethylsiloxane (PDMS), as a low surface energy material, has its molecular chains intertwined within the siloxane network, with methyl groups on its surface arranged outwards, providing extremely low surface energy.
[0052] The synergistic effect of the micro / nano rough structure and low surface energy enables the surface to achieve a superhydrophobic state (water contact angle >150°, roll-off angle <10°), significantly improving the hydrophobic effect of the hydrophobic layer. Some of the siloxane hydroxyl groups in the siloxane network can undergo condensation reactions with the hydroxyl groups on the wood surface to form Si-OC chemical bonds, ensuring a strong bond between the hydrophobic layer and the wood matrix. Simultaneously, the presence of polydimethylsiloxane also endows the hydrophobic layer with good flexibility and weather resistance.
[0053] To better achieve the aforementioned flame-retardant and reinforcing effects, the fiber-reinforcing material accounts for 3% to 15% of the mass percentage of the wood composite material, including but not limited to: 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc. The flame retardant accounts for 10% to 20% of the mass percentage of the wood composite material, including but not limited to: 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc.
[0054] For any of the aforementioned wood-based composite materials, the density of the wood-based composite material is 1.2 g / cm³. 3 ~1.4g / cm 3 .
[0055] The density of the wood matrix can be reduced from less than 1 g / cm³ through hot pressing. 3 Increased to 1.2 g / cm 3 ~1.4g / cm 3 This is because, during the hot pressing process, the cell walls of the wood are compacted, the cellulose molecular chains come closer to each other, forming a large number of intermolecular hydrogen bonds, which significantly reduces the porosity of the material and greatly increases its density.
[0056] A density of 1.2 g / cm³ is the critical value for wood composites to obtain excellent mechanical properties. Below this density, the fiber reinforcement and densification effects are insufficient, and the mechanical properties are difficult to meet the requirements of structural components. 1.4 g / cm³ is the upper limit for taking into account lightweight. Exceeding this density will weaken the weight advantage of wood composites and significantly increase the energy consumption and process difficulty of hot pressing.
[0057] Tests have shown that the wood-based composite material provided in this application has at least the following advantages: (1) Excellent mechanical properties: The use of bamboo fiber reinforcement material makes the tensile strength of wood composite material reach 439MPa and the fracture toughness reach 8.7MJ / m. 3 It is more than 20 times stronger than raw wood, meeting the mechanical strength requirements of automotive exterior parts.
[0058] (2) Excellent fire resistance: The use of nitrogen-phosphorus synergistic flame retardant reduces the peak heat release rate of wood composite materials by 77.7% and the total heat release by 63.6%, which can meet the Class A flame retardant standard. When used in automotive exterior parts, it helps to improve vehicle safety.
[0059] (3) Superhydrophobic and self-cleaning: The hydrophobic layer allows the water contact angle to be as high as 150° or even 161.2°, while the sliding angle is only 3.9°, making it difficult for dirt to adhere, reducing maintenance costs and improving long-term performance.
[0060] (4) Environmental protection and sustainability: Bamboo fiber reinforced material is a renewable material. The carbon emissions during the production process are reduced by more than 90% compared with aluminum alloy. The product can be biodegraded after its service life, thus avoiding environmental pollution.
[0061] (5) Excellent energy absorption characteristics: The natural honeycomb structure of wood provides excellent energy absorption capacity, and the collision energy absorption efficiency is 98% higher than that of traditional aluminum alloy, thus improving the passive safety of the vehicle.
[0062] This application also provides a method for preparing a wood-based composite material, wherein the wood-based composite material is as described in any of the foregoing embodiments, and the method for preparing the wood-based composite material includes the following steps: Step 1: Perform lignin removal treatment on natural wood to obtain a wood matrix with a three-dimensional cellulose skeleton.
[0063] Step 2: Fill the cellulose three-dimensional skeleton of the wood matrix with fiber-reinforced material to obtain the first intermediate.
[0064] Step 3: Fill the skeleton of the first intermediate with flame retardant to obtain the second intermediate.
[0065] Step 4: Perform hot pressing on the second intermediate to obtain wood composite material.
[0066] The method for preparing wood-based composite materials also provided in this application avoids competitive adsorption and agglomeration problems that may occur when multiple components are filled simultaneously by stepwise filling of fiber reinforcement materials and flame retardants, ensuring that each functional component is uniformly distributed and fully exerts its function. Subsequently, hot pressing treatment is used to simultaneously achieve material densification, hydrogen bond reconstruction, and solidification of each component, making the preparation process simple and efficient.
[0067] The preparation steps described above will be illustrated by examples below.
[0068] For step 1, natural wood is subjected to lignin removal treatment to obtain a wood matrix with a three-dimensional cellulose skeleton.
[0069] In some examples, the preparation of a wood matrix includes: The selected natural wood is cut into the required size and softened in hot water at 80-100℃ for 2-4 hours to open up the wood's pore structure, making it easier for subsequent chemical treatment.
[0070] The pretreated wood was immersed in a mixed solution of sodium hydroxide (NaOH) and sodium sulfite (Na2SO3) (mass concentration 2%~5%) for 8~24 hours at 75~85℃. By adjusting the solution concentration and treatment time, the removal rate of lignin and hemicellulose was controlled while preserving the cellulose skeleton structure.
[0071] After the treatment is completed, the wood is repeatedly rinsed with deionized water until it is neutral to obtain a wood matrix with a porous cellulose skeleton.
[0072] Of course, fiber-reinforced materials can also be prepared in advance. In some examples, when the fiber-reinforced materials include bamboo fibers and bamboo cellulose nanofibers, the preparation of the fiber-reinforced materials includes: Preparation of positively charged bamboo fibers: Natural bamboo fibers are surface-modified via a quaternization reaction. Exemplarily, bamboo is deconstructed into bamboo fiber bundles, which are then immersed in an alkaline solution containing 3-chloro-2-hydroxypropyltrimethylammonium chloride (CHPTAC) and reacted at 60–80°C for 3–6 hours. This process grafts hydroxyl groups onto the cellulose molecular chains with quaternary ammonium salt groups, thereby imparting a positive charge to the bamboo fiber surface. After the reaction is complete, the fibers are washed with water until neutral and then dried for later use.
[0073] Preparation of negatively charged bamboo cellulose nanofibers: Bamboo pulp fibers were dispersed in water, and TEMPO catalyst, NaBr, and NaClO were added. The reaction was carried out at room temperature under alkaline conditions at pH=10, selectively oxidizing the primary hydroxyl groups of cellulose to carboxyl groups. After the reaction, the nanofibers were purified by dialysis and then dissociated by high-pressure homogenization or ultrasonic treatment to obtain a suspension of carboxylated bamboo cellulose nanofibers.
[0074] Electrostatic self-assembly: Positively charged bamboo fiber bundles are mixed with a negatively charged bamboo cellulose nanofiber suspension. The two spontaneously combine through electrostatic attraction, and the bamboo cellulose nanofibers are uniformly adsorbed and coated on the surface of the bamboo fibers, forming a bamboo fiber reinforced material. This process requires no adhesives, is environmentally friendly, and results in a strong bond.
[0075] For step 2, the bamboo fiber reinforcement material is filled into the cellulose three-dimensional skeleton of the wood matrix to obtain the first intermediate. This can be done by using a vacuum-pressure impregnation or cyclic impregnation process to place the wood matrix in a solution containing the bamboo fiber reinforcement material, so that the bamboo fiber reinforcement material fills into the cellulose three-dimensional skeleton of the wood matrix.
[0076] For step 3, the flame retardant is filled into the skeleton of the first intermediate to obtain the second intermediate. This can be done by using a vacuum-pressure impregnation or cyclic impregnation process to place the first intermediate in a solution containing the flame retardant, so that the flame retardant fills into the skeleton of the first intermediate.
[0077] For step 4, the second intermediate is subjected to hot pressing to obtain a wood composite material. This can be done by setting hot pressing parameters according to the wood type, target density and thickness, and hot pressing the second intermediate. During the hot pressing process, moisture evaporates, cellulose molecular chains rearrange under pressure and temperature and form a large number of hydrogen bonds, bamboo fiber reinforcement is compacted and fixed, and flame retardant is evenly distributed in the dense structure, finally obtaining a high-density, high-performance wood composite material.
[0078] In some examples, based on the density parameters of the wood matrix mentioned above, the hot pressing process parameters can be exemplarily set as follows: temperature of 120℃~170℃, pressure of 30MPa~80MPa, and time of 5 minutes~15 minutes.
[0079] In conjunction with any of the aforementioned methods for preparing wood-based composite materials, the method for preparing wood-based composite materials provided in this application further includes: After hot pressing, the obtained wood composite material is subjected to surface hydrophobic treatment to form a hydrophobic layer on the surface of the wood matrix.
[0080] Surface hydrophobic treatment can be achieved by methods such as immersion, spraying, and sol-gel, where a treatment liquid containing hydrophobic raw materials is applied to the material surface. For example, when the hydrophobic raw materials include TEOS and PDMS, under ammonia catalysis or acid catalysis, TEOS undergoes in-situ hydrolysis and condensation on the material surface to form a three-dimensional siloxane network, while PDMS molecular chains are entangled and penetrate the network to obtain a hydrophobic layer.
[0081] See in some examples Figure 1 The process steps of the method for preparing wood composite materials provided in this application embodiment can be as follows: Step 1: Raw material preparation and pretreatment Select natural wood with uniform grain and no defects, and cut it into blanks of the required size. Soak the blanks in hot water at 80~100℃ for 2~4 hours to soften them, allowing the wood cell walls to fully swell and open the pore structure, creating conditions for subsequent chemical treatment.
[0082] Step 2: Chemical delignification treatment The softened wood blanks are immersed in a 2%–5% (w / w) NaOH / Na2SO3 mixture and reacted in a water bath at 80°C for 12–24 hours. After the reaction, the wood is removed and repeatedly rinsed with deionized water until the pH of the effluent is neutral, thus obtaining the wood matrix.
[0083] The key to this step is controlling the appropriate removal of lignin: if the removal rate is too low, the pores will not open sufficiently, resulting in poor subsequent filling effects; if the removal rate is too high, the skeleton strength will be damaged, making it prone to collapse and deformation. The lignin removal rate can be 10%~50%, and further, it can be 15%~30%, to balance porosity and skeleton integrity.
[0084] Step 3: Filling with bamboo fiber reinforcement material (i.e., preparing the first intermediate) The filling process employs a vacuum-pressurized cyclic impregnation method. The wood matrix is placed in an impregnation tank, and a vacuum is applied for 10-30 minutes to expel air from the pores. Then, a pre-prepared suspension of bamboo fiber reinforcement is drawn in, and the pressure is increased to 1.0-1.5 MPa and maintained for 30-60 minutes to allow the fiber suspension to fully penetrate the wood skeleton. This vacuum-pressurized cycle is repeated 2-3 times to ensure that the bamboo fiber reinforcement is uniformly and fully filled into the cellulose three-dimensional skeleton. After impregnation, the matrix is removed, the surface liquid is drained, and the first intermediate is obtained.
[0085] Step 4: Flame retardant filling (i.e., preparation of the second intermediate) Using the same vacuum-pressure impregnation process, the first intermediate is immersed in a PEI / APP compound flame retardant solution. The solid content of the flame retardant solution can be adjusted according to the target loading amount, typically 10%~30%. After 2~3 vacuum-pressure cycles, the flame retardant fully penetrates and fills the remaining pores of the wood skeleton. The material is then removed and drained to obtain the second intermediate.
[0086] Step 5: Hot pressing densification treatment The second intermediate was placed in a flatbed hot press for hot pressing densification. The hot pressing parameters were: temperature 130~145℃, pressure 40~45 Bar, and time 5~15 minutes.
[0087] Step 6: Surface hydrophobic treatment The hot-pressed wood composite material undergoes a surface hydrophobic treatment. A TEOS / PDMS treatment solution is prepared by mixing TEOS, PDMS, ammonia, and ethanol in a specific ratio, stirring thoroughly, and then aging for a period of time to form a prepolymer solution.
[0088] The treatment liquid is applied to the surface of the wood composite material by spraying or impregnation. After application, it is cured at room temperature or under mild heating conditions. TEOS is further hydrolyzed and condensed to form a siloxane network, in which PDMS is wrapped, and finally a uniform and transparent hydrophobic layer is formed on the material surface.
[0089] Step 7: Molding and Post-processing Depending on the application requirements of wood composite materials, wood composite materials can also be processed into structural components of specific shapes through processes such as CNC milling, laser cutting, and grinding and polishing.
[0090] This application also provides a wooden structural component, which is prepared using any of the aforementioned wood composite materials.
[0091] The preparation method of this wooden structural component can still be found in [reference needed]. Figure 1 ,like Figure 1 As shown, after the wood composite material is prepared, step 7, molding and post-processing, is further performed. Depending on the application requirements of the wood composite material, it can also be processed into structural components of specific shapes using CNC milling, laser cutting, grinding and polishing processes.
[0092] This wooden structural component uses wood composite material as its base material and can be manufactured into various shapes and specifications through processing methods such as CNC milling, laser cutting, and molding. Thanks to the excellent mechanical properties, flame retardant properties, and weather resistance of wood composite material, this wooden structural component can replace traditional plastic or metal parts and be used in various scenarios requiring strength, fire resistance, and durability.
[0093] The wood structural components provided in this application have all the advantages of the wood composite materials described in this application. For example, their advantages may be as follows: Reliable mechanical properties: Based on high-strength wood composite materials, the structural components have strong load-bearing capacity and good impact toughness, which can meet the needs of various structural applications.
[0094] Green, environmentally friendly and sustainable: Wood composite materials are biodegradable and have a low carbon footprint, which aligns with the concepts of green manufacturing and circular economy, enhancing the environmental image of products.
[0095] Significant weight reduction through lightweight construction: Compared to metal structural components, the weight reduction effect is significant, which helps to reduce the overall weight of equipment and reduce energy consumption.
[0096] Excellent processing performance: Wood is easy to cut, drill, mill and other processes, with high forming accuracy, and can be used to make complex shaped structural parts.
[0097] Unique appearance and texture: It retains the natural texture and warm feel of wood, combining structural function and aesthetic value, thus enhancing the product's quality.
[0098] In some examples, the structural component includes automotive exterior trim. Automotive exterior trim includes, but is not limited to: bumpers, door panels, fenders, side skirts, wheel arches, trunk trim, roof trim, etc.
[0099] The wood composite materials provided in this application can meet various needs of automotive exterior parts. Specifically, the high strength of the wood composite materials meets the requirements for collision safety and structural rigidity; the flame retardant properties of the wood composite materials meet the fire protection standards for automotive interior / exterior parts; the superhydrophobic self-cleaning properties of the wood composite materials adapt to outdoor rain, snow, and dust environments; the lightweight characteristics of the wood composite materials help reduce the weight and energy consumption of the whole vehicle; and the natural wood texture of the wood composite materials enhances the luxury and uniqueness of the interior and exterior.
[0100] Different automotive exterior components can be specifically optimized within the parameter range of the technical solution in this application, based on stress conditions and functional emphasis. For example, bumpers are biased towards high strength and energy absorption characteristics, door panels are biased towards lightweight and aesthetic appeal, and fenders are biased towards weather resistance and stone chip resistance.
[0101] The embodiments of this application compare the performance of automotive exterior parts prepared from its wood composite materials with that of traditional automotive exterior parts, and the results are listed in Table 1.
[0102]
[0103] As shown in Table 1, the wood composite material provided in this application has a high advantage in specific strength, while also possessing excellent flame retardancy and environmental friendliness. Its comprehensive performance surpasses that of traditional plastic exterior parts, and it is significantly superior to metal exterior parts in terms of specific strength and environmental friendliness.
[0104] This application also provides an automobile that includes the aforementioned wooden structural components.
[0105] The automobile is equipped with exterior trim parts made of the wood composite material described in the embodiments of this application. These wood structural parts can be connected and fixed to other parts of the vehicle body by means of clips, bolts, adhesives, etc. The installation method is compatible with traditional exterior trim parts and does not require significant changes to the existing assembly process.
[0106] The application of wooden exterior trim not only brings lightweight and environmental benefits, but its natural material texture can also serve as a differentiated design highlight for automobiles, especially suitable for new energy vehicles, high-end customized models, concept cars and other products that emphasize environmental protection and design.
[0107] In addition, the acoustic properties of wood materials can help improve the noise, vibration, and harshness (NVH) performance of vehicles, thereby enhancing driving safety and comfort.
[0108] Exemplary embodiments of this disclosure will now be described in more detail. While exemplary embodiments of this disclosure are described below, it should be understood that this disclosure can be implemented in various forms and should not be limited to the embodiments set forth herein. Where specific techniques or conditions are not specified in the embodiments, they are performed in accordance with techniques or conditions described in the literature in the art or according to product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0109] It should be noted that the bamboo fiber reinforcing materials involved in the following embodiments all include: bamboo fibers and bamboo cellulose nanofibers bonded to the surface of the bamboo fibers. The flame retardants involved all include polyethyleneimine and ammonium polyphosphate in a mass ratio of 1:2. The hydrophobic layers involved all include: a siloxane network and polydimethylsiloxane molecules wound within the siloxane network.
[0110] Example 1 Example 1 describes the preparation of a wood composite material that can be used to manufacture wooden bumpers that meet low-speed collision regulations, requiring extremely high mechanical strength and impact resistance.
[0111] This wood-based composite material comprises: a wood matrix, fiber reinforcement, a flame retardant, and a hydrophobic layer. The wood matrix is obtained by removing 30 wt% lignin from beech wood with an initial density of 0.72 g / cm³ and possesses a three-dimensional cellulose skeleton. The fiber reinforcement fills within the cellulose skeleton; the flame retardant fills within the cellulose skeleton; and the hydrophobic layer coats the surface of the wood matrix. The fiber reinforcement accounts for 10% of the mass percentage of the wood-based composite material. The flame retardant accounts for 20% of the mass percentage of the wood-based composite material.
[0112] The preparation steps of this wood composite material are as follows: (1) Delignification treatment Beechwood blanks with an initial density of 0.72 g / cm³ were selected and treated with a 4% (w / w) NaOH + Na₂SO₃ mixed solution at 85°C for 20 hours to remove lignin, achieving a removal rate of approximately 30%. This process resulted in higher porosity, providing space for the subsequent filling of other components. After lignin removal, the wood was washed with water until neutral to obtain the wood matrix.
[0113] (2) Impregnation of bamboo fiber reinforced material The wood matrix was placed in a suspension of bamboo cellulose reinforcement material with a mass concentration of 0.8%, and the bamboo cellulose nanofibers were deeply penetrated and evenly distributed inside the skeleton of the wood matrix through a vacuum (-0.095 MPa) / pressurized (1.5 MPa) impregnation process for 3 cycles.
[0114] (3) Flame retardant treatment A flame retardant solution with a solid content of 30% was used to impregnate the flame retardant for 3 hours under a pressure of 1.2 MPa, ensuring that the loading mass percentage of the flame retardant was 20%.
[0115] (4) Hot pressing densification The wood was hot-pressed for 12 minutes at a temperature of 150℃ and a pressure of 50 MPa to densify it to a density of 1.40 g / cm³.
[0116] (5) Surface hydrophobic treatment The surface of wood composite material was treated with a TEOS / PDMS hydrophobic material system to form a hydrophobic layer, thus obtaining the wood composite material.
[0117] A wooden bumper was fabricated using this wood composite material. Tests showed that the tensile strength of the wooden bumper was greater than 450 MPa, meeting the safety requirements under high-speed collisions.
[0118] Example 2 Example 2 describes the preparation of a wood composite material that can be used to prepare pure wood car door panels that emphasize lightweight, aesthetics, and everyday durability.
[0119] This wood-based composite material comprises: a wood matrix, fiber reinforcement, a flame retardant, and a hydrophobic layer. The wood matrix is obtained by removing 20 wt% lignin from black walnut wood with an initial density of 0.66 g / cm³ and possesses a three-dimensional cellulose skeleton. The fiber reinforcement fills within the cellulose skeleton; the flame retardant fills within the cellulose skeleton; and the hydrophobic layer coats the surface of the wood matrix. The fiber reinforcement accounts for 5% of the mass percentage of the wood-based composite material. The flame retardant accounts for 15% of the mass percentage of the wood-based composite material.
[0120] The preparation steps of this wood composite material are as follows: (1) Delignification treatment Black walnut blanks with an initial density of 0.66 g / cm³ were selected and treated with a 3% (w / w) NaOH + Na₂SO₃ mixed solution at 80℃ for 12 hours to remove lignin, with a removal rate of approximately 20%, to obtain suitable porosity and better preserve the natural texture and color of the wood. After lignin removal treatment, the wood was washed with water until neutral to obtain the wood matrix.
[0121] (2) Impregnation of bamboo fiber reinforced material The wood matrix was placed in a suspension of bamboo cellulose reinforcement material with a mass concentration of 0.58%, and the bamboo cellulose nanofibers were deeply penetrated and evenly distributed inside the skeleton of the wood matrix through a vacuum (-0.095 MPa) / pressurized (1.5 MPa) impregnation process for 3 cycles.
[0122] (3) Flame retardant treatment A flame retardant solution with a solid content of 20% was used, and the wood was impregnated at normal pressure for 12 hours to ensure that the flame retardant loading amount reached 15% of the loaded mass of the wood matrix.
[0123] (4) Hot pressing densification The wood was hot-pressed for 8 minutes at a temperature of 135℃ and a pressure of 30 MPa to densify it to a density of 1.20 g / cm³.
[0124] (5) Surface hydrophobic treatment The TEOS / PDMS hydrophobic material system is used to perform surface hydrophobic treatment on wood composite materials to form a hydrophobic layer and obtain wood composite materials. During this process, a matte effect is obtained by controlling the amount of spraying to highlight the natural texture of the wood.
[0125] A car door panel was prepared by molding this wood composite material. The car door panel has a luxurious appearance, is lightweight, and has sufficient durability.
[0126] Example 3 Example 3 describes the preparation of a wood composite material that can be used to manufacture wood fenders, which require complex curved surface forming and long-term weather resistance.
[0127] This wood-based composite material comprises: a wood matrix, fiber reinforcement, a flame retardant, and a hydrophobic layer. The wood matrix is obtained by removing 15 wt% lignin from paulownia wood with an initial density of 0.28 g / cm³ and possesses a three-dimensional cellulose skeleton. The fiber reinforcement fills within the cellulose skeleton; the flame retardant fills within the cellulose skeleton; and the hydrophobic layer coats the surface of the wood matrix. The fiber reinforcement accounts for 3% of the mass percentage of the wood-based composite material. The flame retardant accounts for 15% of the mass percentage of the wood-based composite material.
[0128] The preparation steps of this wood composite material are as follows: (1) Delignification treatment Paulownia wood blanks with an initial density of 0.28 g / cm³ were selected and treated with a 2% (w / w) NaOH + Na₂SO₃ mixed solution at 75°C for 8 hours to remove lignin, with a removal rate of approximately 15%. This process aimed to improve the wood's plasticity for easier shaping while achieving suitable porosity. After lignin removal, the wood was washed with water until neutral to obtain the wood matrix.
[0129] (2) Simultaneous impregnation of reinforcement and flame retardant Bamboo cellulose reinforcement was directly added to a flame retardant solution with a solid content of 20% to obtain a blended solution of reinforcement and flame retardant. The wood matrix was then immersed in the blended solution under normal pressure for 12 hours. The bamboo fiber reinforcement accounted for 3% of the total load, thus moderately improving the strength of paulownia wood while maintaining its lightweight properties.
[0130] (3) Hot pressing The wood was hot-pressed for 15 minutes at 125℃ and 25 MPa to densify it to a density of 1.05 g / cm³, and the shape was replicated using a curved mold.
[0131] (4) Surface hydrophobic treatment A TEOS / PDMS hydrophobic material system was used to perform surface hydrophobic treatment on wood composite materials to form a hydrophobic layer, thus obtaining the wood composite material. During this process, the thickness of the hydrophobic layer was increased to provide stronger resistance to stone impact and ultraviolet radiation.
[0132] Fenders were fabricated using this wood composite material, resulting in extremely lightweight, precisely shaped, and highly weather-resistant fenders.
[0133] The above description is only for the purpose of enabling those skilled in the art to understand the technical solution of this application, and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A wood-based composite material, characterized in that, The wood composite material includes: The wood matrix has a three-dimensional cellulose skeleton; Fiber-reinforced material is filled within the three-dimensional cellulose skeleton; Flame retardant, filled within the three-dimensional cellulose skeleton; A hydrophobic layer is applied to the surface of the wood matrix; The density of the wood composite material is greater than or equal to 1.2 g / cm³. 3 .
2. The wood-based composite material according to claim 1, characterized in that, The fiber-reinforcing material includes bamboo fiber and bamboo cellulose nanofibers bonded to the surface of the bamboo fiber.
3. The wood-based composite material according to claim 1, characterized in that, The wood matrix has a density of less than or equal to 1 g / cm³. 3 It is obtained by partially removing lignin from natural wood.
4. The wood-based composite material according to claim 1, characterized in that, The flame retardant includes at least one of phosphorus-based flame retardants or nitrogen-based flame retardants.
5. The wood-based composite material according to claim 4, characterized in that, The flame retardant includes polyethyleneimine and ammonium polyphosphate.
6. The wood-based composite material according to claim 1, characterized in that, The hydrophobic layer comprises: a siloxane network and polydimethylsiloxane molecules wrapped around the siloxane network.
7. The wood-based composite material according to any one of claims 1-6, characterized in that, The fiber-reinforced material accounts for 3% to 15% of the mass percentage of the wood composite material; The flame retardant accounts for 10% to 20% of the mass percentage of the wood composite material.
8. The wood-based composite material according to any one of claims 1-7, characterized in that, The density of the wood composite material is 1.2 g / cm³. 3 ~1.4g / cm 3 .
9. A method for preparing a wood-based composite material, characterized in that, The wood-based composite material is as described in any one of claims 1-8, and the method for preparing the wood-based composite material includes: Natural wood is subjected to lignin removal treatment to obtain a wood matrix with a three-dimensional cellulose skeleton; A first intermediate is obtained by filling fiber-reinforced material into the three-dimensional cellulose skeleton of the wood matrix. The flame retardant is filled into the skeleton of the first intermediate to obtain the second intermediate; The second intermediate is subjected to hot pressing to obtain the wood composite material.
10. The method for preparing the wood-based composite material according to claim 9, characterized in that, The method for preparing the wood composite material further includes: After hot pressing, the obtained wood composite material is subjected to surface hydrophobic treatment to form a hydrophobic layer on the surface of the wood composite material.
11. A wooden structural component, characterized in that, The wooden structural component is prepared using the wood composite material described in any one of claims 1-8.
12. The wooden structural component according to claim 11, characterized in that, The structural components include automotive exterior parts.
13. A car, characterized in that, The vehicle includes the wooden structural components as described in any one of claims 11-12.